PENYAJIAN INFORMASI BENDA CAGAR BUDAYA DI DAERAH ISTIMEWA YOGYAKARTA DENGAN GIS CLOUD - , KHUSNUL FATHONI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Heritage Objects are natural objects and historical man-made objects which are movable or unmovable, aged at least 50 years, and are considered to have an important value for history, science, and culture. The condition of cultural heritage objects that are located in D.I. Yogyakarta, are well preserved but some of them are abandoned, even in worrying condition. Therefore this project was presenting the information of cultural heritage objects using GIS Cloud. This system is purposed to present cultural heritage information so that everyone know about the cultural heritage objects that are located in D.I. Yogyakarta. Presentation of cultural heritage object information was built from the spatial data input and attribute that was created in shapefile format using Quantum GIS, and additional data such us photographs of cultural heritage objects to clarify these objects. This project is made using GIS Cloud. The processes of The processes of this project are by uploading data shapefile or data photos